Thorax Interactive Learning Objects (Out of Print) - Elizabeth Walker; Edwin Allen; Heather Billings (Association of American Medical Colleges, 2010)
Abstract Introduction This is a collection of 12 self-test exercises related to thorax anatomy including, artery circulation, vein circulation, heart anatomy, and respiratory anatomy. All learning objects are anchored in learning objectives and are interactive, requiring learners to process information and make decisions. These are intended to accompany undergraduate anatomy courses and be used by instructors and students in premedical, predental, nursing, and other health care-related curricula. Methods For each area of anatomy, students may select from a range of exercises including short-answer, matching, and multiple-choice questions. The modules use Flash software to enable a high level of learner interaction with the content, such as the ability to drag-and-drop anatomical structures on line drawings, and checkboxes with structure names for anatomical structure identification on dissected cadavers. In addition, learners may navigate through a thoracic case study that requires student feedback in order to progress through the cases. Immediate feedback is provided to the learner upon selection of a structure in order to reinforce the learning. Results Although no formal study of effectiveness has been conducted, anecdotal evidence indicates that students value and appreciate the interactive learning modules. Discussion The module successfully achieves true interactivity in the educational context, as it both challenges learners to cognitively process basic science information in order to make a decision, and provides immediate feedback about that decision. The Adobe Flash plug-in was chosen as the deployment tool because it was ubiquitous across computer platforms, suitable for the development task, and the necessary expertise was available.